Hubungan Kekuatan Otot Lengan dan Otot Tungkai terhadap Kemampuan Free Throw pada Peserta Ekstrakurikuler Bola Basket - Gempar Al-Hadist; Dede Hermawan; Arif Fajar Prasetiyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was written according to what was on the field, namely that the women's basketball extracurricular participants at SMA Negeri 1 Ciasem when shooting free throws the ball did not reach the basketball hoop, although there were a few who could put the ball in but did not understand the basics. This raises a question that makes the author want to know the relationship between arm and leg muscle strength and free throw ability in female basketball extracurricular participants at SMA Negeri 1 Ciasem. With a total of 14 samples tested and 1x meeting for the test. To find out the relationship between arm and leg muscle strength on free throws, the author used a correlational method to find the relationship. From the results obtained, arm muscle strength has a sig value of 0.463, and leg muscle strength has a sig value of 0.463. This is an answer that arm muscle strength and leg muscle strength are not significant because the variables X1 and This is caused by several factors, namely: 1. The girls' basketball extracurricular coach at SMA Negeri 1 Ciasem does not have a training program. 2. Balance. 3. Eye view. 4. Mental. 5. Height.